Bullying and student wellbeing in Finnish primary schools : a consideration of gender and family affluence - Kim, Dongwoo (2018)
The main purpose of this study is to examine the impact of bullying on student wellbeing. Research has shown devastating consequences of bullying on students’ lives, but few studies address how bullying victimization is associated with different dimensions of student wellbeing. The study also explores the effects of gender and family affluence on student wellbeing and bullying victimization. The participants were drawn from a larger ProKoulu study. Participants were from 2nd grade (N=1339) and 6th grade (N=1232). The results indicate that bullying has negative impacts on all six dimensions of student wellbeing (commitment to school, feeling of justice in school, student-parent relationship, student relations in school, student-teacher relationship in school, and workload in school) in both 2nd and 6th grade students. Among the six dimensions, bullying had the strongest impact on student relations in school. In terms of gender, boys are more likely to report frequent bullying victimization, while girls rated more positively in student wellbeing. Family affluence was weakly associated with student-parent relationship and perceived workload in school in 6th grade. The findings of this study can contribute to developing programs to enhance student wellbeing and alleviate the negative impact of bullying in Finland.